Reduction of aromatic and heteroaromatic azo compounds with hydrazine hydrate [Aromatic ve heteroaromatic bileşiklerin hidrazin hidratla redüksiyonu] - (:unkn) unknown (My University, 2010)
The azo compounds have been reduced with hydrazine hydrate in the presence of a catalyst or without a catalyst. This reaction is an atractive alternate for the reduction of azo functional group to obtain new amines. In this review, the reduction of aromatic or heteroaromatic azo compounds with hydrazine hydrate have been reported.
Keywords: Azo compounds; Hydrazine hydrate; Reduction; Uncatalyzed reduction